Craniofrontonasal syndrome caused by introduction of a novel uATG in the 5′UTR of EFNB1 - Tavares, VL; Kague, E; Musso, CM; Alegria, TGP; Freitas, RS; Bertola, D; Twigg, SRF; Passos-Bueno, MR (Karger, 2018)
Craniofrontonasal syndrome (CFNS) is an X-linked disorder caused by EFNB1 mutations in which females are more severely affected than males. Severe male phenotypes are associated with mosaicism, supporting cellular interference for sex bias in this disease. Although many variants have been found in the coding region of EFNB1, only 2 pathogenic variants have been identified in the same nucleotide in 5′UTR, disrupting the stop codon of an upstream open reading frame (uORF). uORFs are known to be part of a wide range of post-transcriptional regulation processes, and just recently, their association with human diseases has come to light. In the present study, we analyzed EFNB1 in a female patient with typical features of CFNS. We identified a variant, located at c.-411, creating a new upstream ATG (uATG) in the 5′UTR of EFNB1, which is predicted to alter an existing uORF. Dual-luciferase reporter assays showed significant reduction in protein translation, but no difference in the mRNA levels. Our study demonstrates, for the first time, the regulatory impact of uATG formation on EFNB1 levels and suggests that this should be the target region in molecular diagnosis of CFNS cases without pathogenic variants in the coding and splice sites regions of EFNB1.